Boron phytoremediation: Stizolobium aterrimum is tolerant and can be used for phytomanagement of boron excess in soils - Pereira Costa, Beatriz Gonçalves [UNESP]; Justino, Gilberto Costa; Aguiar, Leandro Ferreira; Souza, Lucas Anjos; Camargos, Liliane Santos [UNESP] (Taylor & Francis, 2018)
Soil contamination by toxic elements causes concern and is increasing through industrial development, mining activities and the overuse of chemical fertilisers. Some toxic elements, such as boron, also play a structural role. The present study aimed to evaluate the behaviour of S. aterrimum plants growing in boron artificially contaminated soils. It has been found that S. aterrimum is tolerant to low doses of boron, moderately tolerating doses of up to 240 mg.dm−3. But high doses (doses above the adequate zone) cause decreased plant growth and present symptoms of toxicity, such as foliar chlorosis. The dose of 240 mg.dm−3 can already be considered toxic, since the tolerance index (TI) was less than 50%. The species can be used as a phytoextractor in low doses of boron because it presented a high tolerance index (TI) and demonstrated the ability to uptake and accumulate boron in root tissue.
Keywords: environmental protection; Phytoremediation; soil pollution